2016
DOI: 10.1007/s11192-016-2061-8
|View full text |Cite
|
Sign up to set email alerts
|

Long term productivity and collaboration in information science

Abstract: Funding bodies have tended to encourage collaborative research because it is generally more highly cited than sole author research. But higher mean citation for collaborative articles does not imply collaborative researchers are in general more research productive. This article assesses the extent to which research productivity varies with the number of collaborative partners for long term researchers within three Web of Science subject areas: Information Science & Library Science, Communication and Medical In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…articles, scholarly books, patents), collaboration patterns and other indicators relevant to scholarly publications. In the sciences, publication patterns are shaped through a variety of factors depending on the discipline (Engels et al 2012), such as epistemic cultures (Knorr Cetina 1999), citation cultures (Wouters 1999) and the growing importance of interdisciplinary research and cooperation (Levitt and Thelwall 2016). These factors are integral to science and research, and substantially influence what type of publications are favoured, what publication language is most often used, how many authors prepare publications, and which journals in a given discipline are acknowledged by the academic community as a valid way of communicating research results.…”
Section: Introductionmentioning
confidence: 99%
“…articles, scholarly books, patents), collaboration patterns and other indicators relevant to scholarly publications. In the sciences, publication patterns are shaped through a variety of factors depending on the discipline (Engels et al 2012), such as epistemic cultures (Knorr Cetina 1999), citation cultures (Wouters 1999) and the growing importance of interdisciplinary research and cooperation (Levitt and Thelwall 2016). These factors are integral to science and research, and substantially influence what type of publications are favoured, what publication language is most often used, how many authors prepare publications, and which journals in a given discipline are acknowledged by the academic community as a valid way of communicating research results.…”
Section: Introductionmentioning
confidence: 99%
“…These authors determined that collaboration is not an indispensable requisite for obtaining a high degree of citation, as some of the authors with the highest degree of collaboration also presented the lowest degree of citation. In a more recent study Levitt and Thelwall (2016) reported that researchers who worked in groups of 2 or 3 were generally the most productive, in terms of producing the most papers and citations. Similarly, Bu et al (2018a) concluded that papers written by large groups of researchers tend to have a lower impact, a result that justifies the interest in measuring these variables as control indicators during individual researcher evaluation processes.…”
Section: Discussion Individual Indicators For Scientific Activity Comentioning
confidence: 99%
“…This includes better Internet connectivity in different countries, and improvement in synchronous conferencing and screen/video‐sharing tools such as Zoom GoToMeeting, Skype, Google Hangouts, etc., asynchronous tools such as Google docs which allow for co‐typing in a single document, and cloud‐computing solutions such as Google Drive, Dropbox, etc., which have made it easier for geographically distant collaborators to work seamless on research articles (as also found by Agarwal & Rahim, 2019). International collaboration between universities and other research organizations is beneficial to all, and facilitates funding and publishing (Levitt & Thelwall, 2016).…”
Section: Discussionmentioning
confidence: 99%